2005
DOI: 10.1007/s10512-005-0179-5
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the time for establishing radiation equivalence of high-level wastes

Abstract: The potential harm of long-lived radionuclides estimated as the product of the activity of a radionuclide and the dose coefficient is examined. The potential harm of actinides in high-level wastes is calculated taking account of the harm due to their decay products. At the same time, an analogous calculation is performed for the uranium isotopes 238 U, 235 U, and 234 U consumed in the reactor. The value obtained, which depends on the time, can be regarded as the averted harm. The time for establishing radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…For workers, the maximum yearly uptake of the two isotopes of cesium with mass numbers 137 and 135 differs by only a factor of 10, and the minimum significant specific activity differs by a factor of 1000 (Table 5). We also note that the minimum significant specific activity of natural uranium in equilibrium with the decay products is 1 Bq/g, the average content of uranium in the lithosphere is 4 g/ton, i.e., approximately 0.05 Bq/g, and there are rocks and soils where the radium content is 20 times the value indicated in [18]. These and other data show that NRB-99 must be corrected.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…For workers, the maximum yearly uptake of the two isotopes of cesium with mass numbers 137 and 135 differs by only a factor of 10, and the minimum significant specific activity differs by a factor of 1000 (Table 5). We also note that the minimum significant specific activity of natural uranium in equilibrium with the decay products is 1 Bq/g, the average content of uranium in the lithosphere is 4 g/ton, i.e., approximately 0.05 Bq/g, and there are rocks and soils where the radium content is 20 times the value indicated in [18]. These and other data show that NRB-99 must be corrected.…”
mentioning
confidence: 55%
“…Comparison of the Normative Quantities Used in NRB for Estimating the Radiation Danger of Various Long-Lived Radionuclides[18] …”
mentioning
confidence: 99%
“…The long-lived radionuclides (T 1/2 > 15 yr) present in HLW can be divided into two groups: fission products and transuranium elements. Previous work [1] has shown that the second group is much more dangerous than the first one, and to optimize the storage time and mass of the stored wastes it is desirable to separate out the actinide fraction of the HLW, which depending on the technological process will consist partially or entirely of lanthanides -fission products. It has been shown [2] that perovskite with the composition M I M II O 3 , where M I is a metal ion with ionic radius of about 1 Å and M II is a metal ion with radius close to the ionic radius of titanium in naturally occurring perovskite (CaTiO 3 ) -0.64 Å, can be used to immobilize the actinide fraction.…”
mentioning
confidence: 99%